Mana Whenua, Mana Moana, Mana Tinana, Mana Mōmona - Gillon, Ashlea; Le Grice, Jade; Webber, Melinda; McIntosh, Tracey (New Zealand Sociology, 2026)
E rere ana ngā ngaru, hoki ki te wai whakatau ai. Ko te āio te take. Hoki ki a Hinemoana, ki tōna whakaniko, ki tōna pikopiko, i reira ngā ngako o te mōmonatanga, o te tinana, hei rongoā mō tātou.E tipu, e tū ana ngā maunga, hoki ki te whenua whakatau ai. Ko te āio te take. Hoki ki a Papatūānuku, ki tōna tinana, ki tōna whakaniko, ki tōna pikopiko, i reira ngā ngako o te tinana, o te mōmonatanga, te mōmonatanga o te whenua. Hei rongoā mō tatou.Nō te whenua, nō te moana.Koinā te whakapapa.Tihei Mauri Ora.The ways in which we understand bodies and fatness are complex. While coloniality unduly influences and shapes normative meanings of the body in everyday contexts, Māori conceptualisations of the body and of fatness remain inscribed within the moana, the whenua, te reo Māori and our whakapapa. These understandings provide insight into fatness and bodies from a Māori worldview. Our whakaaro in this article speaks into Māori ways of being and knowing, including meanings of mōmonatanga as bountiful, rich, fertile, and powerful. This article develops an expansive and holistic Māori understanding of bodies and fatness from the whenua, from the moana, from our whakapapa.